Fatigue Analysis of Inter-Array Power Cables between Two Floating Offshore Wind Turbines Including a Simplified Method to Estimate Stress Factors - Dennis Beier; Anja Schnepf; Sean Van Steel; Naiquan Ye; Muk Chen Ong (Journal of Marine Science and Engineering, 2023)
The use of floating offshore wind farms for electrical energy supply is expected to rise significantly over the coming years. Suspended inter-array power cables are a new design to connect floating offshore wind turbines (FOWTs) with shorter cable lengths than conventional setups. The present study investigates the fatigue life of a suspended power cable with attached buoys connecting two spar-type FOWTs. Typical environmental conditions for the North Sea are applied. The nonlinear bending behavior of the power cable is considered in the analysis. Fatigue assessment is performed using the numerical software OrcaFlex based on stress factors obtained from cross-section analysis. An effective method for obtaining the stress factors is proposed for early engineering design stages and compared with the finite element software UFLEX simulation results. The simplified method delivers similar results for axial tension loads and conservative results for bending loads compared with results obtained from the finite element software. Stress components resulting from curvature variation are identified as the main contributors to fatigue damage. The most critical locations along the power cable for fatigue life are close to the hang-off points.